The effect of impulsivity, self-disgust and self-compassion in borderline features in adolescence: Study of sex differences - Carreiras, Diogo (2020)
Background: Adolescence is a developmental stage with biological, psychological, and social changes that will influence the individual functioning in adulthood. Recently, research on borderline personality disorder (BPD) has been focusing on dysfunctional and inflexible features in early ages, since a personality disorder does not appear suddenly in adulthood. The developmental path should be better understood and explored. Objective: Accordingly, the current study aimed at analyzing the contribution of psychological processes, specifically impulsivity, self-disgust, and self-compassion, for understanding borderline features in adolescence. Methods: This study had a cross-sectional design and a sample of 440 adolescents from the general population (278 girls and 162 boys), with ages ranging between 14 and 17 years. In SPSS, we conducted Student’s t-tests, Pearson correlations, and linear regressions. Results: Girls presented higher levels of self-disgust and borderline features in comparison with boys and lower levels of self-compassion. Regression models to test the predictive value of impulsivity, self-disgust and self-compassion on borderline features were significant. The model explained 43% of borderline features for boys and 57% for girls. For girls, all variables (impulsivity, self-compassion, and self-disgust) presented a significant contribution, and for boys, only impulsivity and self-compassion were significant predictors. Conclusions: These results added evidence of important variables to understand better borderline features in adolescents and identified sex differences in these psychological mechanisms. This study has important implications for research, clinical practice, and prevention.